Bending fatigue strength design method for machine components with complex geometries (Fracture and Structural Integrity, 2018)
The purpose of this study is to devise a bending fatigue strength evaluation method that can be widely used for any machine component under the consideration that bending fatigue breakage depends on the initiation of a surface fatigue crack, namely, the conditions for the initiation of a fatigue crack can be used as the criteria for bending fatigue strength design. The specially designed and manufactured three-point bending specimens with crowned round notches are used in bending fatigue experiments. The obtained bending fatigue strengths are expressed as the maximum actual stress at the critical point, which increases with decreasing notch radius. Considering the effects of the stress distribution on the bending fatigue strength, we present a method for estimating the tension fatigue strength of a smooth specimen, which is shape-independent fatigue strength and can be applied to bending fatigue strength design for machine components with complex geometries.
Keywords: Bending fatigue strength; Fatigue crack initiation; Stress distribution; Shape-independent fatigue strength